Characterization and genomic analysis of two Aeromonas phages - Jiang, Li ling; Liu, Chang; Liu, Guang feng; Tao, Xiu hua; Zhang, Hong Sai; Zhang, Yue; Chen, Yuyu; Li, Meng yao; Jiang, Jing zhe; Chen, Hong peng (Frontiers in Microbiology, 2025)
Phages, as viruses that specifically infect certain bacteria, have great research value in the prevention and control of bacterial diseases. Bacteria of the genus Aeromonas are widely distributed in aquatic environments and are important zoonotic pathogens that can cause a variety of diseases. In this study, two virulent phages, AhC3_1 and AsC4_1, were successfully isolated using bacteria from the genus Aeromonas. The evolutionary relationships of the two phages were analyzed using methods such as phylogenetic analysis and average amino acid identity (AAI) analysis, and their biological characteristics were assessed through approaches including one-step growth curve assay and temperature tolerance testing. The results showed that the genome sequences of phages C3 and C4 were 232,884 bp and 45,983 bp in length, respectively, with G + C contents of 44.36% and 50.11%. Both belong to double-stranded circular DNA viruses. Phages C3 and C4 have been classified within two novel viral genera, provisionally designated as “Aynavirus” and “Asnavirus,” respectively. Additionally, both C3 and C4 exhibited good stability in different temperature and pH conditions. The latent period of C3 was 10 min, with a burst size of 32 PFU.cell−1. The in vitro antibacterial curve showed that when the multiplicity of infection (MOI) was 10−3, C3 could exert a strong inhibitory effect on Aeromonas hydrophila for up to 10 h. The latent period of C4 was less than 10 min, with a burst size of 1,250 PFU.cell−1. At an MOI of 10−1, C4 could exert a strong inhibitory effect on Aeromonas salmonicida for up to 15 h. In summary, the two phages isolated in this study have the potential to serve as potential therapeutic agents for aquaculture diseases and provide valuable data for research on antibacterial infections.